The Influence of Visual Perception on Navigation and City Image: A Landmark Study in Pekanbaru - Fitriany, Fitriany; Fuadi, AlBusyra; Wongso, Jonny; Marison, Artian Ferry; Kusumah, Dadang Puja (SIGMA TEKNIKA, 2025)
This study analyzes the influence of public visual perception on urban navigation and city image through the role of landmarks in Pekanbaru. The background stems from the declining visual legibility of the city due to rapid spatial development and architectural homogenization. Five main landmarks were examined: An-Nur Grand Mosque, Zapin Monument, Soeman HS Library, the Riau Governor’s Office, and Idrus Tintin Art Pavilion. A mixed-method approach was applied using questionnaires from 105 respondents, field observations, and Multidimensional Scaling (MDS) analysis. The results indicate that An-Nur Grand Mosque and Soeman HS Library function as the city’s visual-affective anchors with high legibility and civic pride. Zapin Monument serves as a directional marker with strong cultural symbolism, while the Governor’s Office is visually dominant but weak in collective identity. Idrus Tintin Art Pavilion represents cultural symbolism but plays a limited navigational role. The study concludes that Pekanbaru’s city image emerges from the interaction of architectural quality, navigational function, and symbolic-emotional values, recommending enhanced visibility, integrated wayfinding systems, and cultural revitalization in urban planning.